Valvular interstitial cells suppress calcification of valvular endothelial cells. Issue 1 (September 2015) - Hjortnaes, Jesper; Shapero, Kayle; Goettsch, Claudia; Hutcheson, Joshua D.; Keegan, Joshua; Kluin, Jolanda; Mayer, John E.; Bischoff, Joyce; Aikawa, Elena
Abstract Background Calcific aortic valve disease (CAVD) is the most common heart valve disease in the Western world. We previously proposed that valvular endothelial cells (VECs) replenish injured adult valve leaflets via endothelial-to-mesenchymal transformation (EndMT); however, whether EndMT contributes to valvular calcification is unknown. We hypothesized that aortic VECs undergo osteogenic differentiation via an EndMT process that can be inhibited by valvular interstitial cells (VICs). Approach and results VEC clones underwent TGF-β1-mediated EndMT, shown by significantly increased mRNA expression of the EndMT markers α-SMA (5.3 ± 1.2), MMP-2 (13.5 ± 0.6) and Slug (12 ± 2.1) (p < 0.05), (compared to unstimulated controls). To study the effects of VIC on VEC EndMT, clonal populations of VICs were derived from the same valve leaflets, placed in co-culture with VECs, and grown in control/TGF-β1 supplemented media. In the presence of VICs, EndMT was inhibited, shown by decreased mRNA expression of α-SMA (0.1 ± 0.5), MMP-2 (0.1 ± 0.1), and Slug (0.2 ± 0.2) (p < 0.05). When cultured in osteogenic media, VECs demonstrated osteogenic changes confirmed by increase in mRNA expression of osteocalcin (8.6 ± 1.3), osteopontin (3.7 ± 0.3), and Runx2 (5.5 ± 1.5). The VIC presence inhibited VEC osteogenesis, demonstrated by decreased expression of osteocalcin (0.4 ± 0.1) and osteopontin (0.2 ± 0.1) (p < 0.05). Time course analysis suggested that EndMT precedes osteogenesis, shown by an initial increase of α-SMA and MMP-2 (day 7), followed by an increase of osteopontin and osteocalcin (day 14). Conclusions The data indicate that EndMT may precede VEC osteogenesis. This study shows that VICs inhibit VEC EndMT and osteogenesis, indicating the importance of VEC–VIC interactions in valve homeostasis.